Motors of change?: elite actors and the Spanish transition to democracy (1975-1981) - Hill, Christopher James (2006)
This thesis examines the methodology prevalent in the analysis of democratic transitions, focusing upon the case study of Spain. Although current literature provides a detailed description of actions taken by elite actors during transition periods and the resultant outcomes, it fails to adequately connect these two factors. This thesis seeks to address the gap in the current literature and to underline the necessity for an explanatory methodology to take into account an amalgamation of approaches.